2011
DOI: 10.1111/j.1461-0248.2011.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected consequences of control: competitive vs. predator release in a four-species assemblage of invasive mammals

Abstract: Invasive species are frequently the target of eradication or control programmes to mitigate their impacts. However, manipulating single species in isolation can lead to unexpected consequences for other species, with outcomes such as mesopredator release demonstrated both theoretically and empirically in vertebrate assemblages with at least two trophic levels. Less is known about the consequences of species removal in more complex assemblages where a greater number of interacting invaders increases the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 41 publications
5
147
0
Order By: Relevance
“…Stokes et al (2009) in Australia, and Harris and Macdonald (2007) in the Galápagos Islands, demonstrated that native rats (R. fuscipes and Nesoryzomys swarthi, respectively) suffered from interference competition rather than resource competition with the larger, non-native black rats. Furthermore, removal of black rats can result in population increases in coexisting rodents such as house mice (Harper and Cabrera 2010;Ruscoe et al 2011). The average body masses of the three coexisting rodents in our study differed 4-10 fold.…”
Section: Discussionmentioning
confidence: 59%
“…Stokes et al (2009) in Australia, and Harris and Macdonald (2007) in the Galápagos Islands, demonstrated that native rats (R. fuscipes and Nesoryzomys swarthi, respectively) suffered from interference competition rather than resource competition with the larger, non-native black rats. Furthermore, removal of black rats can result in population increases in coexisting rodents such as house mice (Harper and Cabrera 2010;Ruscoe et al 2011). The average body masses of the three coexisting rodents in our study differed 4-10 fold.…”
Section: Discussionmentioning
confidence: 59%
“…Stokes et al (2009) in Australia, and Harris and Macdonald (2007) in the Galápagos demonstrated that native rats (Rattus fuscipes and Nesoryzomys swarthi, respectively) suffered from interference competition with nonnative R. rattus. Furthermore, removal of R. rattus can result in population increases in coexisting nonnative rodents on Pacific islands, which has been observed with M. musculus in New Zealand (Ruscoe et al 2011) and in the Galápagos (Harper and Cabrera 2010).…”
Section: Impact On Vertebrate Communitiesmentioning
confidence: 92%
“…Also, to increase the efficiency of this action as well as avoiding unmotivated culling, an evaluation of the spatial scale where measures are necessary is highly recommended. Even though predator control has been successful in the case of Arctic fox conservation (Angerbjörn et al 2013), there are examples of unexpected consequences of predator removal (Ruscoe et al 2011). Therefore, continuous assessment of removal strategies and consequences is central.…”
Section: Implications For Red Fox Management and Arctic Fox Conservationmentioning
confidence: 99%